DESIGN AUTOMATION STORAGE PENGHAMBAT LAJU KOROSI SPARE PART MESIN DAN HASIL PRODUKSI PEMESINAN - Wijayanto, Hendi Lilih; Hidayat, Hidayat; Siswanto, Yudi; Pratigto, Setiarto; Yusdianto, Yusdianto (Universitas Nahdlatul Ulama Blitar, 2025)
The development of technology is increasingly advanced in this modern era, making human life inseparable from the use of machines. These machines must have various spare parts made from steel/iron. In addition, the machining production of these machines is made of steel / iron which can be corroded. Corrosion is a decrease in metal quality caused by the environment or chemicals and affects the condition of a material. The way to overcome the occurrence of corrosion in iron, especially engine spare parts and machining production results is by designing and making corrosion rate inhibitor storage automation as a storage medium for engine spare parts and machining production results. The design of this machine is carried out in several stages, namely planning, design, manufacture, and testing. This research was conducted with the parameters of the results of spraying lubrication and temperature control. From the results of experiments that have been carried out, this storage automation is able to spray lubrication in accordance with the timing that has been set and is able to control the temperature in the storage so that the tool is able to inhibit the rate of corrosion on the workpiece.